Integrated management of interstitial lung disease associated with rheumatoid arthritis - A case report - Buduru Sreenivasa Prasad; Darshana G Korgaokar; Deepti Basavraj Bagewadi (Wolters Kluwer Medknow Publications, 2021)
Interstitial lung disease (ILD) is a broad term for a large group of disorders that leads to fibrosis of the lungs. A female of 58 years with ILD associated with rheumatoid arthritis was well managed by integrated treatment of Ayurveda and physiotherapy. This is shown in our case report where in the symptoms of the patient were relieved by more than 80% by the combined approach of treatment. The patient consulted for complaints of intermittent cough and exertional dyspnea for 1 month and pain and stiffness of joints for the last 3 years. This report emphasizes the importance of integrated management of ILD associated with RA by Ayurvedic therapies such as sadhyo-virechana (instant purgative therapy) vaitarana basti (special enema with revival property) and ayurvedic oral medications with physiotherapy procedures such as postural breathing exercise, postural drainage, and deep breathing exercise. Although the disease is not completely curable, integrated approach could provide convenient and a better way of treatment which relieved the symptoms and also improved the quality of life.